Building the Future: Village Innovation Towards Sustainability - Sahar, Nurman; Syukur, Alam Tauhid; Mauliana, Deasy (Universitas Negeri Makassar, 2023)
A great and successful innovation is one that endures even after the leadership has changed and the managers have moved. The organizer or person in charge must maintain the current level of innovation. The local government must apply sustainable improvements. In addition to striving to improve the welfare of the village community, the sustainability of village innovations employs a notion of sustainable development management. As a result, community welfare as a result of village innovation can increase development that is felt not only by the current generation, but also by the community in the future. This study applied a qualitative approach with literature review method. Interviews are used to acquire data. The literature review was carried out by examining the sustainability of the Mallari village government's Village Innovation in South Sulawesi Province, Bone Regency. The purpose of this research is to determine the sustainability of village innovation from a variety of perspectives, including economic, social, and environmental. The result of the study showed that the sustainability of village innovations implemented in Mallari village is influenced by a variety of factors, including social, economic, and environmental factors.